2013
DOI: 10.1016/j.automatica.2013.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Provably safe and robust learning-based model predictive control

Abstract: Controller design faces a trade-off between robustness and performance, and the reliability of linear controllers has caused many practitioners to focus on the former. However, there is renewed interest in improving system performance to deal with growing energy constraints. This paper describes a learning-based model predictive control (LBMPC) scheme that provides deterministic guarantees on robustness, while statistical identification tools are used to identify richer models of the system in order to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
446
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(451 citation statements)
references
References 66 publications
3
446
0
2
Order By: Relevance
“…Ideally, provably safe controllers should also be least restrictive, which means in the context of a driver-assist system that the controller constrains the possible actions of the human driver as little as possible. Due to the computational complexity of the task, the design of provably safe, least restrictive controllers remains a challenge and can in general only be done approximately, see for instance [9,3,11]. However it has been shown that a number of ground transportation systems have the so-called inputoutput order preserving property, in which case exact solutions are possible, see [4,12,5] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Ideally, provably safe controllers should also be least restrictive, which means in the context of a driver-assist system that the controller constrains the possible actions of the human driver as little as possible. Due to the computational complexity of the task, the design of provably safe, least restrictive controllers remains a challenge and can in general only be done approximately, see for instance [9,3,11]. However it has been shown that a number of ground transportation systems have the so-called inputoutput order preserving property, in which case exact solutions are possible, see [4,12,5] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…Like robust control, LBMPC can deal with uncertainty directly, but also allows the designer to specify performance objectives to optimize and explicitly incorporates on line model updates to further improve performance. LBMPC is compatible with many learning techniques; previous work has employed a modified NadarayaWatson estimator with Tikhonov regularization (Aswani et al, 2012a) and a semi-parametric regression estimator (Aswani et al, 2012b).…”
Section: Overviewmentioning
confidence: 99%
“…A recently developed control technique with roots in MPC, adaptive, and learning-based control is called learning based model predictive control (LBMPC) (Aswani et al, 2012a). It seeks to combine attributes of MPC (most notably, the ability to enforce constraints, which encode safety requirements) with elements of adaptive or learning schemes which promise to improve performance by improving system models based on data obtained on-line.…”
Section: Learning-based Mpc (Lbmpc)mentioning
confidence: 99%
See 1 more Smart Citation
“…Designing controllers under reachability analysis and safe learning are well-studied methods that allow specifying safety and reachability properties, while learning the optimal strategy online [32,33,15,3,1]. However, finding the reachable set is computationally expensive, which makes these approaches impractical for most interesting tasks.…”
Section: Related Workmentioning
confidence: 99%